Risk-sharing in Rural Pakistan (The Pakistan Development Review, 1996)
Risk-sharing is a fundamental form of economic behaviour. It can occur through formal insurance markets, informal family arrangements, community support, legal institutions (such as bankruptcy), or government tax-transfer programmes. Whatever the mechanism used to share risk, the extent of risk mitigation can greatly influence the welfare of all members of society. Understanding the degree of risk-pooling in society is important for policy-makers, since insufficient risk pooling may provide a basis for government intervention. Alternatively, if risks are being pooled adequately without the help of the government, government risk-sharing may be redundant. This study explores the implications of the risk-sharing model, namely, that households which pool risks, either through formal markets or informal personal arrangements, experience correlated changes in their consumption through time. It conducts tests of within-village, across-village, within-district, and across-district risksharing using a new Pakistani panel data set—the Pakistan Food Security Management Survey—collected by the International Food Policy Research Institute (IFPRI), Washington, D. C. Unlike studies for other Less Developed Countries (LDCs), these tests find very little or almost no evidence of risk-sharing among unrelated individuals within- and across-villages in the rural sector of Pakistan.